AML1-ETO inhibits acute myeloid leukemia immune escape by CD48. Issue 4 (21st March 2021) - Wang, Zhiding; Guan, Wei; Wang, Mengzhen; Chen, Jinghong; Zhang, Linlin; Xiao, Yang; Wang, Lixin; Li, Yonghui; Yu, Li
Abstract: The t(8;21)(q22;q22) translocation is the most common chromosomal translocation in acute myeloid leukemia (AML), and it gives rise to acute myeloid gene 1 (AML1)-myeloid transforming gene 8 (ETO)-positive AML, which has a relatively favorable prognosis. CD48 is a favorable prognosis factor that is downregulated in AML patients. AML can escape immunosurveillance of natural killer (NK) cells by decreasing CD48 expression. The correlation between AML1-ETO and CD48-mediated immune evasion is not well understood. Here, we show that AML1-ETO can increase CD48 expression, which is regulated by AML1-ETO/P300-mediated acetylation. AML1-ETO can inhibit AML immune escape from NK cell recognition and killing by increasing CD48 expression. This study describes a novel mechanism by which AML1-ETO can inhibit AML immune escape by increasing CD48 acetylation, thereby providing new evidence about AML patients with AML1-ETO oncogene infusion having better clinical outcomes.